Preservice Teachers Facilitating a Discussion With Elementary Student Avatars Before Facilitating It With Real Students - Lottero-Perdue, Pamela; Cimino, Karen; Brandeberry, Julia (Innovations in Science Teacher Education, 2023)
In this article, we share our innovation in which we used backward design to develop a scenario for use within the Mursion mixed-reality (MR) upper elementary simulated classroom environment to enable preservice teachers (PSTs) to practice facilitating an ambitious group discussion before facilitating that discussion to students in their field placement. The third-year elementary PSTs were enrolled in a course in which they taught a fourth-grade, NGSS-aligned unit that focused on the external and internal structures of sea turtles and how an injury to one or more of those structures could impact their growth, survival, behavior, or reproduction. To enhance the unit, we added a nonfiction text, Karl’s New Beak (Nargi & Popham, 2019), that examines the ramifications on survival, behavior, and reproduction faced by an Abyssinian ground hornbill missing most of his lower beak. At the end of the unit, each PST facilitated a discussion to elicit connections their students made between key ideas in the unit and text about how an injury to an animal impacts its survival, behavior, or reproduction. We share key elements of scenario design and how the PSTs prepared for, implemented, and debriefed from the MR simulated discussion. We also summarize and provide examples from the PSTs’ reflections on how the simulated experience prepared them to facilitate the same discussion with their small groups of fourth graders. For teacher educators who have access to the Mursion system, we provide our scenario and recommendations on how to begin utilizing this technology.